EUS-FNA versus Biliary Brushings and Assessment of Simultaneous Performance in Jaundiced Patients with Suspected Malignant Obstruction - Oppong, Kofi; Raine, Dan; Nayar, Manu; Wadehra, Viney; Ramakrishnan, Subramaniam; Charnley, Richard M (JOP. Journal of the Pancreas, 2010)
Context Individuals with suspected malignant biliary obstruction commonly undergo ERCP for drainage and tissue sampling via biliary brushings. EUS with EUS-FNA facilitates staging and potentially more accurate tissue sampling. Objective The aim is to compare the diagnostic performance of EUS-FNA and ERCP with biliary brushings (ERCP-BB) in the diagnosis of pancreatobiliary carcinoma and the utility of combining the two procedures under conscious sedation. Design Retrospective analysis of a prospectively maintained database. Patients Thirty-seven patients with suspected malignant obstructive jaundice underwent 39 paired procedures, either combined (n=22) or within a few days (n=17). Results Using strict cytological criteria the sensitivity of EUS-FNA in the diagnosis of malignancy was 52.9% (95% CI: 35.1-70.2%) versus 29.4% (95% CI: 15.1-47.5%) for ERCP-BB. Combining the two tests improved sensitivity to 64.7% (95% CI: 46.5-80.3%) which was significantly better than ERCP-BB alone (P=0.001) but not EUS-FNA alone (P=0.125). When both procedures were performed under the same conscious sedation, there was a significant difference (P=0.031) between the sensitivity of EUS-FNA (52.6%; 95% CI: 28.9-75.6%) and that of ERCP-BB (21.1%; 95% CI: 6.1-45.6%). When both procedures were performed together the mean±SD in-room time was 79±14 min (range: 45-105 min). Two of the patients (9.1%) had a complication. Conclusions In patients undergoing EUS-FNA and ERCP-BB under the same sedation, EUS-FNA was significantly more sensitive in diagnosing malignancy. Combining the results of both tests improved diagnostic accuracy. Combining therapeutic ERCP and EUS-FNA under the same conscious sedation is feasible, with a complication rate similar to that of ERCP alone. Image: Freeman Hospital. Newcastle upon Tyne, United Kingdom.